The Influence of Interactive Website Discovering Authentic Personal Style Among Grade 12 Nizamia High School - Kalika Naira Salsabil; Risky Mulia Kusumah Dewi (International Journal Labs, 2026)
The rapid development of digital technology and social media has significantly influenced adolescent identity formation, particularly in how teenagers perceive themselves and express their individuality. Excessive exposure to online trends, idealized lifestyles, and social comparisons may encourage adolescents to conform to external expectations rather than develop authentic self-expression. This research aims to design and develop an interactive website that assists Grade 12 students in discovering their personal style based on personality characteristics while providing guidance through fashion recommendations, styling tips, and visual references. This study employs a qualitative descriptive approach involving a literature review and user evaluation through a feedback questionnaire. The research participants consisted of Grade 12B students at Nizamia High School who explored the developed website and provided feedback regarding its usability, clarity, relevance, and effectiveness. The results indicate that the interactive website successfully supported students in understanding their personal style and expressing themselves with greater confidence. The website achieved an overall average satisfaction score of 4.1 out of 5, with the highest evaluations observed in quiz clarity (4.6) and confidence in self-expression (4.3). The findings suggest that integrating personality exploration, fashion education, and digital technology can provide an effective approach to supporting adolescent identity development. In conclusion, the interactive website serves as a valuable digital tool that promotes self-awareness, authenticity, and confidence among students while offering potential applications in educational technology for youth development.